OPTIMIZING ELEMENTARY SCHOOL SCIENCE LEARNING OUTCOMES THROUGH THE USE OF MULTIPLE APPLICATIONS AND STUDENTS’ LEARNING STYLES - Wawan Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The quality of elementary science learning remains a concern due to low student engagement and the limited alignment between instructional strategies and students’ learning characteristics, resulting in suboptimal learning outcomes. This study aims to examine the effect of multiple application-based learning and students’ learning styles on science learning outcomes, as well as their interaction. A quantitative quasi-experimental design was employed involving 60 students divided into experimental and control groups selected through simple random sampling. Data were collected using observation, questionnaires, and tests, and analyzed using multiple linear regression with prerequisite tests of normality and homogeneity. The results show that multiple application-based learning significantly improves science learning outcomes compared to conventional methods (p < 0.05), while differences in learning styles (auditory, visual, kinesthetic) are not statistically significant. In addition, no significant interaction effect is found between instructional method and learning styles, indicating that the multiple application approach has a stronger direct influence on learning outcomes. These findings suggest that integrating multiple platforms such as LMS, WhatsApp Group, and Telegram can enhance student engagement and conceptual understanding in elementary science learning, and future research is recommended to explore broader assessment approaches and additional moderating variables.